Control of a Nonsquare Multivariable System Using Pseudoin-verse Model-Based Static Output Feedback - Zhiteckii, L.S.; Azarskov, V.N.; Sushchenko, O.A.; Yanovsky, F.J.; Solovchuk, K.Yu. (Cybernetics and computer engineering, 2020)
The purpose of the paper is to answer the question: is there the SOF control based on the pseudoinverse concept to stabilize some first-order multivariable system with nonsquare gain matrix? Results. The pseudoinverse model-based control leading to static output feedback is proposed to reject unmeasured disturbances. The optimality and robustness properties of such controller are established. Numerical examples and simulation results are presented to support theoretical study. Мета роботи — дати відповідь на запитання: чи існує регулятор типу SOF, в основу якого покладено концепцію псевдообернення, аби стабілізувати деяку багатовимірну систему першого порядку з прямокутною матрицею коефіцієнтів підсилення? Результати. Аби придушити невимірювальні збурення, запропоновано керування, яке базується на методі псевдооберненої моделі. Цей метод формально приводить до реалізації статичного зворотного зв'язку. Встановлено умови оптимальності та робастності такого регулятора. Для підтвердження теоретичного дослідження наведено числові приклади та результати моделювання.